RATING ESTIMATIONS OF THE ENTERPRISES: PROBLEMS AND MODELING - Kravets, Tatyana (Ekonomika, 2009)
In modern times improvement of the estimation techniques related to the productivity of economic objects y is topical. The article deals with the problems of construction of the rating systems for the estimation of enterprises not related to the financial sector of the economy according to the results of their activity for a calendar year. yea. In order to construct the aggregated indicators for the estimation of the efficiency of the enterprise activity it proposes to unite thepossibilities of the classical financial analysis and the methods of the multidimensional statistical analysis. The created indicators accumulate the information on the initial indicators and are a convenient base for the construction of the rating estimations of enterprises.